Barongan Blora Story "Gegering Alas Jati Wengker" And Its Relevance to Character Education - Egita Widya Astuti; Isnaini Nur Rohmatun; Fagusta Renata Putri (Javanologi: International Journal of Javanese Studies, 2024)
Character education needs to be taught to children from an early age and needs to be improved. Character education can be taught through culture, one of the cultures that contains character education values is Barongan art. Barongan has ethical values that can be studied more deeply. This research uses a descriptive qualitative method with a literary sociology approach. The result of this research is that Barongan art contains character education such as religion, honesty, tolerance, peace-loving, friendship, discipline, hard work, creativity, independence, democracy, curiosity, and love for the country.